2016
DOI: 10.1183/13993003.01282-2015
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus damages the alveolar barrier by disrupting epithelial cell tight junctions

Abstract: A major cause of respiratory failure during influenza A virus (IAV) infection is damage to the epithelial-endothelial barrier of the pulmonary alveolus. Damage to this barrier results in flooding of the alveolar lumen with proteinaceous oedema fluid, erythrocytes and inflammatory cells. To date, the exact roles of pulmonary epithelial and endothelial cells in this process remain unclear.Here, we used an in vitro co-culture model to understand how IAV damages the pulmonary epithelialendothelial barrier. Human e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
3
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(179 citation statements)
references
References 41 publications
(67 reference statements)
9
164
3
3
Order By: Relevance
“…A recent study reported IAV infection interrupts the tight junction formation in an in vitro alveolar culture model comprising immortalized epithelial cells25. In our study, however, the well differentiated tracheal and bronchial epithelia retain their barrier function.…”
Section: Discussioncontrasting
confidence: 69%
“…A recent study reported IAV infection interrupts the tight junction formation in an in vitro alveolar culture model comprising immortalized epithelial cells25. In our study, however, the well differentiated tracheal and bronchial epithelia retain their barrier function.…”
Section: Discussioncontrasting
confidence: 69%
“…To determine the effect of hypoxia as a profibrotic injury to distinct lung epithelial cells, four different cell types derived from proximal and distal lung epithelium were exposed to hypoxia. These include NuLi-1 cells: primary bronchial epithelial cells; H441 cells: derived from bronchoalveolar acinar region, which maintains alveolar and club cell-like features that exhibit features of AEC2s; 26 A549 cells: originating from AEC2s; and primary murine AEC2s. Hypoxia increased mRNA levels of a host of profibrotic genes, including PDGFB (platelet-derived growth factor B), TGF-β , TNF-α (tumor necrosis factor- α ), EDN1 (endothelin-1), and PAI-1 (plasminogen activator inhibitor-1) (Figures 1d–g) in each cell type.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the possibility exists that other hypoxia-associated signaling pathways such as Notch, Hedgehog, and Wnt signaling may participate in progression of PF. 26,50,51 While AE-IPF remains a major cause of mortality in IPF patients, patients with previous histories of lung infections and injury may also be prone to developing PF due to sustained hypoxia signaling in the lung. Therefore, we propose galectin-1 as an important mediator of profibrotic events in the lung and a viable therapeutic target in patients suffering from fibrotic lung diseases, including IPF.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells, whilst not the primary target of influenza virus in humans, play an important role in disease pathogenesis (Teijaro et al, 2011; Short et al, 2013, 2014, 2016). During severe influenza virus infection, pulmonary endothelial cells produce cytokines which drive pulmonary lesions and mortality (Teijaro et al, 2011).…”
Section: A Role For Glycemic Oscillationsmentioning
confidence: 99%